2017
DOI: 10.1097/jac.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Physician Perception of the Role of the Patient Portal in Pediatric Health

Abstract: The patient portal, increasingly available to patients, allows secure electronic communication with physicians. Although physician attitude toward the portal plays a crucial role in patient adoption, little information regarding physician opinion of the portal is available, with almost no information gathered in the pediatric environment. Using a mixed-methods approach, physicians in a large pediatric medical facility and integrated delivery network were surveyed using an online quantitative questionnaire and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Enhanced quality of care following EHR/PHR adoption was suggested [17,24,27,43,45,46,49,57,64,67,75,84,85,107,111,112,115,128,131,133,135,146,150,153]. A randomized trial suggested a significantly lower prevalence in all-cause 30-day readmissions in patients who adopted PHR as compared to non-adopters [88].…”
Section: Quality Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced quality of care following EHR/PHR adoption was suggested [17,24,27,43,45,46,49,57,64,67,75,84,85,107,111,112,115,128,131,133,135,146,150,153]. A randomized trial suggested a significantly lower prevalence in all-cause 30-day readmissions in patients who adopted PHR as compared to non-adopters [88].…”
Section: Quality Of Carementioning
confidence: 99%
“…Better communication between patients and providers was reported as a benefit following the implementation of EHRs/PHRs [32,34,38,42,44,69,86,87,102,134,146,147,153]. Physicians recognized the value of being able to share patient-centered information with patients using EHRs [34,143], while clinicians perceived that new communication channels such as messaging through EHRs should improve communication between patients and providers [45].…”
Section: Communicationmentioning
confidence: 99%
“…Another concern was the workflow impact due to portal implementation. In one study, participating providers indicated that the portal implementation did not have a negative impact on their salary; however, 43% of the same participants believed that the portal increased their workload [ 41 ]. Similar findings were presented by Cajander et al [ 42 ], as the nurses in the study described how patients called and sent messages for the same question, which led to increased workload because of duplication of services.…”
Section: Resultsmentioning
confidence: 99%
“… Alt-text: Unlabelled box In a study of pediatricians practicing in a large medical facility, 43% believed the portal increased their workload overall, but 80% found it led to a reduction in telephone calls and valued the ability to send messages to patients any time of day/night. 29 In addition, clinicians believe written instructions may be easier to interpret and remember than oral instructions. 29 Patient portals may further be used to improve communication regarding care goals and indications for hospitalizations.…”
Section: Benefits Of Using Patient Portalsmentioning
confidence: 99%